Revision of the Chinese species of the leafhopper genus Dayus Mahmood(Hemiptera: Cicadellidae: Typhlocybinae: Empoascini), with description of three new species - Qin, Dao-Zheng; Zhang, Ya-Lin (Zootaxa, 2007)
The Chinese sepcies of the typhlocybine genus Dayus Mahmood are revised. A total of five species, including three new species—lii n.sp, lamellatus n.sp and membranaceus n.sp from Fujian Province are described, and a key to Chinese Dayus species is included.